Si llevas un ratón a la escuela - Numeroff, Laura Joffe; Bond, Felicia; Mlawer, Teresa ([New York] : Scholastic, 2002)
Follows a boy and his mouse through a busy day at school.
Translation of: If you take a mouse to school.
Keywords: Schools -- Fiction; Mice -- Fiction; Spanish language materials; Espanol